CONTROLE DO DENGUE: CARACTERIZAÇÃO DOS CRIADOUROS DE Aedes aegypti (DIPTERA, CULICIDAE) E PARTICIPAÇÃO DAS MULHERES NAS CAMPANHAS DE PREVENÇÃO EM CAXIAS, MA - Neres, Irene Alves Silva (2009)
This study aimed to evaluate the levels of infestation of Aedes aegypti, and participation of women in the dengue prevention campaign in districts located in peripheral areas of Caxias Maranhão. The collections were made during the dry season in the months August to October of 2007 and rainy season from February to April of 2008, with home visits in 800 buildings in the neighborhoods: Fazendinha, Salobro, Pirajá and cauldrons of 200 homes by neighborhood in which made the inspection of all potential breeding containers of A. aegypti. Recorded the amount of larvae and pupae and / or other factors related to breeding such as the amount of water and containers of positive exposure to the sun, beyond the collection of adult mosquitoes. Closed questionnaires were applied addressing knowledge about A. aegypti and dengue main measures of the 200 women residing in four districts. The results showed that in the dry season were recorded 35 positive containers and rainy 84, showing significant difference between seasons (X² = 29.87, df = 1, p <0001) and group storage container was predominant in both seasons. 3529 immatures forms were found during the dry season and 17,827 in the rainy season. As the exposure of positive containers in the sun it was observed that the containers protected from the sun in two seasons were the most productive, showing percentages above 70% to 60% of larvae and pupae. Regarding the volume of water contained in the containers was positive that in the dry season, those that had prevailed over 100 liters of water with a yield of 73.42% of immature, while in the rainy season from 11 to 50 liters were the majority with 38.53% of immature. Generally women who have interviewed showed satisfactory level of knowledge about dengue, with results significantly higher among women of the neighborhood cauldrons, which was recorded the lowest yield of immature, as the Tukey test (p> 0.05). The results of this study show information about the productivity of immature Aedes aegypti and characteristics peculiar to the breeding of preferred vector, pointing also to involvement of women in the prevention of dengue, serving as a basis for improving the program for control of this virus in the region.